PEG matrix enables cell-mediated local BMP-2 gene delivery and increased bone formation in a porcine critical size defect model of craniofacial bone regeneration - Wehrhan, Falk; Amann, Kerstin Ute; Molenberg, Aart; Lutz, Rainer; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2012)
Purpose: This study addressed the suitability of a polyethylene glycol (PEG) matrix as scaffold for cell-mediated local BMP-2 gene transfer in a calvarial critical size defect (CSD) model. Materials and methods: PEG matrix (degradation time 10 days) and PEG membrane (degradation time 120 days) were used in the pig calvarial model. Cylindrical (1 × 1 cm) CSD (9 per animal; 20 animals) were filled with: (i) HA/TCP, covered by PEG membrane (group 1); (ii) HA/TCP, mixed with PEG matrix (group 2); and (iii) HA/TCP mixed with BMP-2 transfected osteoblasts and PEG matrix (group 3). BMP-2/4 gene transfer: liposomal in vitro transfection of BMP-2/V5-tag fusion-protein. Quantitative histomorphometry (toluidine blue staining) after 2, 4 and 12 weeks assessed bone formation. Semiquantitative immunohistochemistry estimated the expression of BMP-2 and V5-tag. Results: Group 3 showed significantly higher new bone formation than groups 1, 2 at 4 (P < 0.05) and 12 (P < 0.02) weeks. BMP-2-V5-tag was detected for 4 weeks. BMP-2 expression in group 3 was higher compared to all other groups after 2 and 4 (P < 0.02) weeks. Conclusions: The PEG matrix serves as scaffold for cell-mediated BMP-2 gene delivery in guided bone regeneration facilitating cell survival and protein synthesis for at least 4 weeks. Local BMP-2 gene delivery by PEG matrix-embedded cells leads to increased bone formation during critical size defect regeneration. © 2011 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2024-05-13
Keywords: BMP-2; Bone regeneration; Critical size defect; Gene transfer; PEG